2021
DOI: 10.1002/hpm.3132
|View full text |Cite
|
Sign up to set email alerts
|

Association between health expenditures, economic growth and environmental pollution: Long‐run and causality analysis from Asian economies

Abstract: This study examines the association between health expenditures, economic growth (EG) and environmental pollution in Asia both at panel and country level. The separate impact of EG and environmental pollution on public and private health expenditures (PRHEs) are also examined. In doing so the panel cointegration tests with the level break, common correlated effects mean group and heterogeneous panel causality test are employed. The study covers 20 Asian economies and time-period from 1995 to 2017. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…As such, following the ongoing international debates on air pollution, there are substantial health and economic costs related to smog and haze, and the health burden is expected to increase dramatically with global warming (Johnston et al., 2021) 42 . In this regard, to improve public health by reducing ambient air pollution has become a global issue (Nasreen, 2021) 45 . According to the Global Burden of Disease 2019, fine particulate pollution in the outdoor environment and inside homes caused by using solid fuels for cooking and heating killed 6.4 million people in 2019 and caused 93 billion days lived with illness (for more information of this report, one could refer to https://www.healthdata.org/gbd/2019.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, following the ongoing international debates on air pollution, there are substantial health and economic costs related to smog and haze, and the health burden is expected to increase dramatically with global warming (Johnston et al., 2021) 42 . In this regard, to improve public health by reducing ambient air pollution has become a global issue (Nasreen, 2021) 45 . According to the Global Burden of Disease 2019, fine particulate pollution in the outdoor environment and inside homes caused by using solid fuels for cooking and heating killed 6.4 million people in 2019 and caused 93 billion days lived with illness (for more information of this report, one could refer to https://www.healthdata.org/gbd/2019.…”
Section: Discussionmentioning
confidence: 99%
“…42 In this regard, to improve public health by reducing ambient air pollution has become a global issue (Nasreen, 2021). 45 According to the Global Burden of Disease 2019, fine particulate pollution in the outdoor environment and inside homes caused by using solid fuels for cooking and heating killed 6. [47][48][49] However, in many cities, air pollution rapidly returned to pre-pandemic levels as soon as the restrictions for the epidemic were relaxed (Wang and Yang, 2021).…”
Section: Citymentioning
confidence: 99%
“…In the case of Turkey, the cointegration analysis demonstrated a unidirectional and significant association between health expenses and economic growth (9). In Asian economies, Nasreen (10) observed positive associations between economic growth and environmental pollution on health expenditures. The findings depicted that the magnitude of the coefficient of environmental pollution is higher than economic growth and bidirectional causality exists between economic growth and health expenses.…”
Section: Renewable Energy Use Household Waste Urban Population and Pu...mentioning
confidence: 91%
“…For omstance, it ican be observed from the above mentioned literature that the pollution level and wastes are playing a substantial role in human health declination (16,39). As a matter of fact, the G6 economies are still using carbon intensive energy resources, which although provides higher economic, along with the increase in public heath expenditure (10). Thus, it can be observed that both the wastes and economic growth could have a role in the health expanditures, which is relevant to study empirically.…”
Section: Data and Model Specificationmentioning
confidence: 99%
See 1 more Smart Citation